UNCOVER THE HIDDEN MEANING OF FIGURATIVE LANGUAGE FOUND IN JASON DERULO SONG LYRICS - Nosi, Yohanes (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
AbstractFigurative language is a language that is used by figures of speech to convey the message or meaning to someone by spoken or written language. Figurative language is generally used in a poetry, song, novel or film. The objectives of this study are to find out types and meaning of figurative language in Jason Derulo song lyrics. There are two theories that used in this study. First, theory by Knickerbocker and Reninger (1974) is used to find out types of figurative languages in Jason Derulo song lyrics. Second, theory by Leech (1981) to find out the meaning of figurative languages in Jason Derulo song lyrics. The writer collected the data by listening the songs, reading the scripts, underling and classifying the lyrics, and taking note of figurative language. The writer analyzed the data descriptively by using qualitative method. There are six types of figurative language found in Jason Derulo song lyrics, they are hyperbole (15), simile (5), paradox (2), personification (2), irony (2), synechdoche (1). The writer found that Hyperbole is the most dominant type of figurative languages used in Jason Derulo song lyrics. Keywords: figurative language, meaning of figurative language.